Chapter 5: Kaitiakitanga: Land, People and Resource Management - Kawharu, Merata (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: environment; history; kaitiakitanga; resource management; social conditions; social life and customs

The Foreshore and Seabed Act: Five years on, where to from here - Whare, Tracey (Māori and the environment: kaitiaki, 2010)
Keywords: citizenship; environment; environmental policy; kaitiakitanga; print only; social life and customs; taiao; water management

Chapter 10: Feast or Famine: Customary Fisheries Management in a Contemporary Tribal Society - Tuuta, Evelyn (Waitangi Revisited, 2005)
Keywords: crown policy; environment; government relations; history; kaitiakitanga; land tenure; māori rights; race relations; rangatiratanga; resource management; tiriti o waitangi/treaty of waitangi

Māori Urban Protest Movements - Taonui, Rawiri (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: discrimination; foreshore and seabed act 2004; government relations; hikoi ki waitangi; history; kaitiakitanga; land march; māori womens welfare league; nga tamatoa; parihaka; poverty; protest; racism; rangatiratanga; resistance; social conditions; springbok tour protests; takaparawhau bastion point; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; tāngata whenua; urbanisation

Māori Interests and Rights: Four Sites at the Frontier - Bargh, Maria; Jones, Carwyn (Public Policy and Governance Frontiers in New Zealand, 2020)
Keywords: crown policy; government; iwi politics; kaitiakitanga; kāwanatanga; māori rights; rangatiratanga